Marginalization of Women in Higuchi Ichiyou's Nigorie Short Story: A Feminism Studies - Salma Nabila; Fajria Noviana (Universitas Dian Nuswantoro, 2021)
The purpose of this study is to describe the marginalization experienced by women in Higuchi Ichiyou's short story Nigorie, and the effects it causes. This research focused on marginalization because marginalization is the root of various unfair treatments experienced by women. As a literature study with the feminism approach, data in the form of dialogues, acts, and events related to women in this short story were analyzed based on Lorber’s and Fakih’s theory of gender inequalities, through the point of view of feminist literary criticism. As the result, it is known that the marginalization experienced by women who work in brothels has resulted in other unfair treatments, which in Fakih's opinion can be categorized as gender inequalities. Such unfair treatments are in the form of impoverishment, putting women in a lower position than men, negative labeling, violence, and double workload. Marginalization and various unfair treatments experienced by women in this short story, which gives the impression that the society in this short story doesn’t consider women as human beings in general, are the manifestations of hegemonic patriarchism that is deeply rooted in the life of the Japanese nation.